DIGITAL STORYTELLING INFLUENCING SUSTAINABLE CONSUMPTION INTENTIONS AMONG GENERATION Z - Rikka Pratiwi Walga; Diah Natalisa; Ahmad Maulana; Welly Nailis (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The rapid growth of e-commerce has transformed consumer behavior while creating environmental challenges through excessive consumption and fast fashion. Digital storytelling has emerged as a communication strategy to enhance environmental awareness and promote sustainable consumption. This study examines the effect of digital storytelling on sustainable consumption intention through environmental awareness in purchasing sustainable fashion and accessories on Shopee. A quantitative explanatory approach was employed using data collected through an online questionnaire from 100 Generation Z respondents in Palembang City selected by purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The results show that digital storytelling positively and significantly affects environmental awareness (β = 0.449, p < 0.001) and sustainable consumption intention (β = 0.393, p < 0.001). Environmental awareness also positively influences sustainable consumption intention (β = 0.510, p < 0.001) and mediates the relationship between digital storytelling and sustainable consumption intention. These findings support the Stimulus-Organism-Response (SOR) theory and provide practical implications for e-commerce businesses in designing effective sustainability-oriented marketing communication strategies.